2017
DOI: 10.29313/gmhc.v5i3.2175
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Stadium Hipertensi dengan Derajat Perlemakan Menggunakan Indeks Hepatorenal Sonografi

Abstract: AbstrakHipertensi merupakan prekursor perkembangan perlemakan hati nonalkoholik. Modalitas pencitraan USG paling banyak digunakan untuk menegakkan diagnosis perlemakan hati nonalkoholik. Saat ini dikembangkan teknik USG menggunakan parameter indeks hepatorenal sonografi yang dihitung dengan program software ImageJ dan digunakan untuk memprediksi derajat perlemakan hati. Penelitian ini bertujuan mengetahui hubungan antara stadium hipertensi dan derajat perlemakan hati nonalkoholik menggunakan indeks hepatorenal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 18 publications
2
0
1
Order By: Relevance
“…While Ryoo et al showed the distribution of NAFLD patients in Korea was very high in normal-mild degrees at 95.44%, moderate degrees at 4.45%, and severe degrees at 0.11%. Although our results differed from those other studies, all studies had more populations with mild to moderate degrees of steatosis and less prevalent severe degrees of steatosis [21].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While Ryoo et al showed the distribution of NAFLD patients in Korea was very high in normal-mild degrees at 95.44%, moderate degrees at 4.45%, and severe degrees at 0.11%. Although our results differed from those other studies, all studies had more populations with mild to moderate degrees of steatosis and less prevalent severe degrees of steatosis [21].…”
Section: Discussioncontrasting
confidence: 99%
“…This study also observed that 56.1% of the subjects were female. Other study in Indonesia such as Marina et al noted that 56% of their subjects were female and identified a significant association between female and severity of NAFLD and also Rengkung, et al reported a higher proportion of females, accounting for 67% of their study population [20,21].These findings support the theory proposed by other studies, which more commonly occurs in women, specifically those experiencing menopause, owing to the deficiency of anti-inflammatory oestrogen [5,20,22].…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation